First equation is: x - y = 12
x = 12 + y
Now, substitute this in 2nd equation,
2x - 3y = 27
2(12+y) - 3y = 27
24 + 2y - 3y = 27
-y = 27 - 24
y = -3
In short, Your Answer would be -3
Hope this helps!
Answer:
so they dont get cramps or chairly horses
Step-by-step explanation:
Driving 70 miles per hour.
Slow your speed means decrease in speed=
70+(-15)=70-15=55 miles/ hr
And then return to speed of 70 miles/hr means
add 15 miles to the speed.
We get
70+(-15)+15 =70 miles / hr
Answer:
True
Step-by-step explanation:
IV is the most useful (even though all will work)
To find the y-intercept, take x=0 and substitute it into the equations.
We can see that if x=0, you can very easily observe that option IV reduces to
y = 0 + 0 - 24 = -24.
Hence (0,-24) is the y-intercept